Economic analysis of use of pessary to prevent preterm birth in women with multiple pregnancy (ProTWIN trial). (7th August 2014) - Liem, S. M. S.; van Baaren, G. J.; Delemarre, F. M. C.; Evers, I. M.; Kleiverda, G.; van Loon, A. J.; Langenveld, J.; Schuitemaker, N.; Sikkema, J. M.; Opmeer, B. C.; van Pampus, M. G.; Mol, B. W. J.; et al.
<x xml:space="preserve">Abstract</x> Linked Comment: Ultrasound Obstet Gynecol 2014; 44: 252–252